Ion source and vacuum system for Bendix Mass Spectrometer - Bendix Corporation (1970)
Close-up view of the ion source and vacuum system attachment designed for use with a Bendix Model MA-004 Time-of-Flight Mass Spectrometer. An oscilloscope, a laboratory instrument commonly used to display and analyze the waveform of electronic signals, is visible on the left-hand side of the apparatus. The Time-of-Flight Mass Spectrometer (TOFMS) was the flagship analytical instrument of the Bendix Corporation.
Keywords: Oscilloscopes; Scientific apparatus and instruments; Spectrometer industry; Mass spectrometry; Time-of-flight mass spectrometry; Bendix Corporation; Ion sources; Mass spectrometers